Pengaruh Rebranding Terhadap Corporate Image Pada Hotel AP Premier Batam - Anisa, Siti; Suyuthie, Hijriyantomi (CV. ITTC INDONESIA, 2025)
This research purposes is to reveal the rebranding impact on image of corporate at the AP Premier Batam hotel. This research type included in research by quantitative through approach of causal associative, data collected through questionnaires distributed to 100 hotel guests sampled for research and in taking the sample, nonprobability sampling techniques in the form of purposive sampling are used. The Likert scale is used as a way to find out how valid and reliable the questionnaire is as a tool for data collected. The analysis for data was done using normality test, linearity, and simple linear regression tests through a level of significance is 0.05. The findings showed that rebranding has a significant influence on corporate image.